A pullout test for the near surface mounted CFRP-concrete bond characterization - Sena-Cruz, José (2007)
To characterize the bond behavior between concrete and CFRP strips, a pullout test is proposed. The developed test setup was used in an experimental program to evaluate the influence of the bond length and the width of slits on the bond behavior. The present work describes the pullout test setup, the carried-out tests and presents and analyzes the most significant obtained results.